Carl E. Swartz, Chairman, Institute of Metals Division, A.I.M.E. - AIME AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
THE year 1940 was an important one in the life of Carl Swartz. At the annual Institute meeting in February of that year, he was inducted into the office of Vice-Chairman of the Institute of Metals Division, and a few months later he assumed another and possibly even more important responsibility-he became the son-in-law of Robert H. Leach, genial vice-president of Handy and Harman, who had just ended his term as Chairman of the Division. The young man who took on this dual obligation in 1940, and who is now commander-in-chief of I.M.D., was born near Danville, Ill., and graduated with honors from the University of Illinois in 1923. (Ed. note: It's a small world. About the time Carl was a freshman in high school at Danville, or slightly before, the University of Illinois students held beer parties in Danville's hotel. We know; we were there.) Continuing his education at another of our fine Middle-Western colleges, Carl received his Master's degree from the University of Wisconsin and his Ph.D. from the same school in 1926. For the next nine years he worked in that splendid training school for non-ferrous metallurgists-the research laboratory of the American Smelting and Refining Co., at Barber, N. J., leaving there in 1935 to take the position of metallurgist of the Cleveland Graphite Bronze Co. in Cleveland, where he is still working (in a modern, air-conditioned office and laboratory) today.